Korelasi Karakter Morfologis dengan Fisiologis Biji Famili Asteraceae di Kaki Gunung Ungaran - Olivia, Theresia Bianca Lucretia; Suedy, Sri Widodo Agung; Saptiningsih, Endang (Universitas Gadjah Mada, 2025)
The Asteraceae family has a wide distribution supported by its adaptive capabilities, including seed morphological traits that influence physiological performance. This study aims to determine the morphological characteristics, physiological performance of seeds, and their correlation in members of the Asteraceae family at the foothills of Mount Ungaran. The findings of this study can also be applied and provide opportunities for further research on seed physiology, particularly in Asteraceae species. The observed parameters in this study include morphological traits (growth habit, achene type, achene length, pappus type, and pappus length) and physiological traits (maturation period, imbibition, germination percentage, germination rate, mean germination time, and vigor) in Asteraceae species at the foothills of Mount Ungaran. The study employs analysis of variance (ANOVA) and Principal Component Analysis (PCA) to assess the significant influence of species differences on seed physiological traits and the strong correlation between morphological and physiological characteristics. Species variation significantly affects seed trait diversity, with morphology playing a crucial role in determining physiological performance and supporting adaptive strategies for survival.